Recirculating Images of the “Terrorist” in Postcolonial Museums: The Case of the National Museum of Struggle in Nicosia, Cyprus - Koureas, Gabriel (My University, 2015)
This chapter discusses the National Museum of Struggle in Nicosia, Cyprus, and its exhibitionary strategies, especially the insistence of its instigator and first director on portraying the consequences of the uprising and the torture regime adopted by the colonial authorities. Rather than promoting the visitor's empathetic response or voyeuristic experience, the images of the mutilated male body graphically repeat the trauma. They create a space where an embodied witnessing can take place and provide the opportunity for the renegotiation of the traumatized body and masculinity in the context of the specific historical circumstances of the violence inflicted by the British colonial regime. In doing so the museum also offers an opportunity to understand through the legacy of the colonial past the intertwined conflict between Greek and Turkish Cypriot communities
Keywords: National Museum of Struggle; Colonial authorities; Cyprus; Trauma